Work Friends: A Commentary on Laura Rosenbury's Working Relationships - Ethan J. Leib (Washington University Journal of Law & Policy, 2011)
This Essay offers the author's insights regarding the Laura Rosenbury's primary research focuses on intimacy and relationships in the workplace. The author says that Rosenbury emphasizes the understanding of intimate networks at work to enrich anti-discrimination norms in the workplace. He states the importance of Rosenbury's primary research agenda to draw one's attention to the reality of what happens at work. It also discusses Mark Granovetter's theory in strengthening the weak ties at work.
Keywords: Work -- Sociological aspects; Human sexuality; Intimacy (Psychology); Interpersonal relations; Work environment